2017
DOI: 10.1007/8904_2017_36
|View full text |Cite
|
Sign up to set email alerts
|

Triheptanoin: A Rescue Therapy for Cardiogenic Shock in Carnitine-acylcarnitine Translocase Deficiency

Abstract: Carnitine-acylcarnitine translocase (CACT) deficiency is a rare long-chain fatty acid oxidation disorder (LC-FAOD) with high mortality due to cardiomyopathy or lethal arrhythmia. Triheptanoin (UX007), an investigational drug composed of synthetic medium odd-chain triglycerides, is a novel therapy in development for LC-FAOD patients. However, cases of its safe and efficacious use to reverse severe heart failure in CACT deficiency are limited. Here, we present a detailed report of an infant with CACT deficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…For the solute carrier family 25 member 20 (SLC25A20 or CACT), a key carnitine-acylcarnitine translocase exchanging for free carnitine across the mitochondrial membrane in mitochondrial beta-oxidation, little information has been acknowledged on its pathophysiologic mechanisms in CVD except for several case reports about the CACT-deficiency in cardiomyopathy, arrythmias and cardiogenic shock ( 40 42 ). However, the current study found for the first time a markedly up-regulation of SLC25A20 transcriptional level in doxorubicin-induced HF, which was further validated with a 1.74-fold change in a HF cohort compared to the healthy control.…”
Section: Discussionmentioning
confidence: 99%
“…For the solute carrier family 25 member 20 (SLC25A20 or CACT), a key carnitine-acylcarnitine translocase exchanging for free carnitine across the mitochondrial membrane in mitochondrial beta-oxidation, little information has been acknowledged on its pathophysiologic mechanisms in CVD except for several case reports about the CACT-deficiency in cardiomyopathy, arrythmias and cardiogenic shock ( 40 42 ). However, the current study found for the first time a markedly up-regulation of SLC25A20 transcriptional level in doxorubicin-induced HF, which was further validated with a 1.74-fold change in a HF cohort compared to the healthy control.…”
Section: Discussionmentioning
confidence: 99%
“…[ 22 ] In addition, triheptanoin (UX007), a novel investigational drug composed of synthetic medium-chain triglycerides (MCT), has recently been used as a compassionate use protocol for the emergency management of patients with several FAO disorders and severe cardiomyopathy. Mahapatra et al [ 23 ] described a case of an infant with CACTD admitted in severe metabolic crisis that devolving into cardiogenic shock who was successfully treated by triheptanoin.…”
Section: Discussionmentioning
confidence: 99%
“…White matter abnormalities are common in this condition although the manifestation does not always correlate with disease course [7,18]. .Survival in early onset CACT deficiency is rare [4,19,20]. Multi-organ failure and death is the usual reported outcome.…”
Section: Discussionmentioning
confidence: 99%